INVESTIGATION OF LAKE HAZAR WATER QUALITY ACCORDING TO PHYSICAL AND INORGANIC CHEMICAL PARAMETERS - Unlu, Ayhan; Coban, Fatih; Tunc, M. Sara (Gazi Univ, Fac Engineering Architecture, 2008)
There is a continuous relationship between a lake and its surrounding land because lakes receive drainage waters from rather large land parts. Lakes constitute the most sensitive water group among surface waters against pollution. Lake Hazar is located southeast of Elazig. Formed on the East Anatolia Fault Zone, it is one of the most important tectonic lakes of our country. It was declared as B class wetland of international importance by Environmental Ministry in 1994. Furthermore, the lake and its surroundings were declared as a tourism area by Council of Ministers. In this study, analysis of physical and inorganic-chemical parameters of water samples taken from five different depths at nine sampling points were carried out for Lake Hazar. Its quality was determined according to the categories of the continental water sources in Water Pollution Control Regulation(WPCR) in Turkey and were also compared with eutrophication control limitation values. According to WPCR classification, Lake Hazar was found to be the first and third class water quality. However, it was in the fourth class water quality according to total phosphorus level. Total phosphorus values exceeded eutrophication control limitation values. A continuous observation programme of the lake will provide rather useful knowledges for environmental management.
Keywords: Lake Hazar; physical and inorganic-chemical parameters; water pollution; eutrophication